2021
DOI: 10.24093/awej/vol12no4.2
|View full text |Cite
|
Sign up to set email alerts
|

Digital Platforms in the Emergency Remote Education: the Students’ Preferences

Abstract: One positive side of the Covid-19 pandemic is the unprecedented opportunity it has offered to the Higher Education Institutions to experience digital learning like never before. During the pandemic, Distant Learning platforms, including Learning Management Systems and Video Conferencing Platforms, have been ubiquitous, and no single institution survived without them during the pandemic. Hence, one of the critical lessons that should be learned is the students’ experiences with these platforms. This study aims … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Al Shammari (2021) examined the reasons for learners' preferences for the two leading online learning platforms in Saudi Arabia -Blackboard and Zoom -during the pandemic. He found that learners preferred Zoom to Blackboard due mainly to the ease of use, and mobility (ability to access on smartphones or mobile app).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al Shammari (2021) examined the reasons for learners' preferences for the two leading online learning platforms in Saudi Arabia -Blackboard and Zoom -during the pandemic. He found that learners preferred Zoom to Blackboard due mainly to the ease of use, and mobility (ability to access on smartphones or mobile app).…”
Section: Discussionmentioning
confidence: 99%
“…The perceived benefits of remote learning (Cardullo et al, 2021;Lech & Johnson, 2021), and learner expectations as regards the features of videoconferencing that supports effective learning (Berges, 2021;Minhas et al, 2021) were also examined. In addition to these are an assessment of learner preference factors which influence the choice of videoconference platform (H. Al Shammari, 2021;Islam et al, 2020).…”
Section: Analysis Model: the Extended Tam Instrumentmentioning
confidence: 99%
“…This potential of reaching out to distant geographical spaces has transformed remote teaching into a highly welcome opportunity in times of crisis. Moreover, in terms of language teachers, digital platforms have been found to be easily accessible and suitably tailored to their needs [16,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…According to Mishra et al [35], the effects of workload, a lack of digital competency, and a lack of knowledge of digital pedagogy on staff stress are all being studied. Although there has not been much research on online education in emergency situations, as most studies have focused on distance learning [36,37,[45][46][47][48][49][50][51][52][53], the current pandemic has demonstrated that educational settings must take a proactive approach to ensure that their students receive the best education possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation